The Effect of Profitability and Liquidity on Financial Distress in The Sub Sector Property Listed on The Exchange Stok Indonesia (IDX) in 2018 - Bill Schara Marbun; Harman Malau (Universitas Batanghari Jambi, 2022)
The goal of this research is to learn more about profitability, liquidity, and financial distress, as well as how they affect profitability and liquidity in the face of financial distress. For the 2018 period, this study was conducted in sub-sector property companies listed on the Indonesian stock exchange, and the sample selection process used purposive sampling to get a total of 50 samples. This study mixes a descriptive approach with a quantitative approach. A ratio scale is used to measure the dependent and independent variables. A ratio scale is used to measure the dependent and independent variables. Logistic regression is a statistical data analysis method that uses descriptive statistics, classification results, Hosmer Test and Lemeshow's Goodness of Fit, Nagelkerke R Test, Parameter Significance Test Individual, and Simultaneous significance test. Profitability has a significant influence on financial distress of 0.018, liquidity has a significant effect on financial distress of 0.005, and there is also a significant effect on profitability and liquidity on financial distress with a significance value of 0.000, according to the study's findings.